Necesidad de reformar el artículo 10 del título primero, capítulo IV, de la ley de régimen tributario interno, en relación a la deducción de el pago del impuesto a la renta - Curiel López, Evelyn Marlene (2015)
This research is framed by the theme "The Right on Finance's activity and Tax of State." The aims were to perform an analytical, legal and doctrinal study on the Financial Legal System and Tax, specifically relating to the “Need to Reform Art 10 of the Internal Tax Regime Law with respect to personal expenses as an employee, to deduct the payment of income tax?" We used a qualitative methodology to get to know the problem essence. This methodology is participatory, and is able to determinate in a good percentage of those affected by problem. And finally permit to generalize the public servant's views of some institutions. Within the results obtained by applying the survey, 67% of respondents stated that the deductible expenses for the payment of income tax are not full covered. They say that only certain groups are covered, such as housing, education, food and clothing. And other expenses have not included, such as utility bills, payment to housing for live their children in case of spouses separation, the school fees of their children when theirs studies far away, daily diet because the market does not get bills. All are expenses, but not all are deductible. This research concluded that is necessary include in the legal record the "Reform Art 10 of the Internal Tax Regime Law with respect to personal expenses as an employee, to deduct the payment of income tax" Taking in consideration social reality to achieve an endogenous and sustainable tax process.